Perbedaan Hasil Belajar Kemampuan Pemecahan Masalah Matematika Siswa Yang Diajar Dengan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Dan Team Games Tournament (TGT) Kelas IX MTS PP. Tarbiyah Islamiyah Hajoran Tahun Pelajaran 2020/2021 - Laroibafihi Tanjung, Rusydi Ananda, Reflina (Pusdikra Publishing, 2021)
One of the students' mathematics learning outcomes is determined by the students' mathematical problem solving abilities. Students' mathematical problem solving abilities can be formed well through the application of learning models. This study aims to determine the differences in the results of students' mathematical problem-solving abilities who are taught using the NHT and TGT cooperative learning models in the matter of powers and roots. The research method used is quasi-experimental. The population in this study were all students of class IX MTs PP. Tarbiyah Islamiyah Hajoran T.P 2020/2021. The sampling technique in this research is random sampling. The sample in this study consisted of two classes, namely IX-A totaling 40 people as the experimental class I (Numbered Head Together class) and 40 students from class IX-B as the experimental class II (Team Games Tournament class). The research instrument used consisted of students' mathematical problem solving ability test questions in the form of initial tests and final tests. Based on statistical hypothesis testing with a t-test at a significant level of 0.05, the results obtained -tcount is smaller than -ttable (-2.7111<-2.0210), so it can be concluded that the results of this study indicate: there are differences in the type of cooperative learning model NHT and TGT on students' mathematical problem solving abilities in grade IX MTs PP. Tarbiyah Islamiyah Hajoran T.P 2020/2021.